HEMATOLOGY PARAMETERS OF THE WHITE RAT (Rattus norvegicus) IN VARIOUS PHYSIOLOGICAL CONDITIONS OF REPRODUCTION - Sumiaty Aiba; Livana Dethris Rawung (Indonesian Biodiversity Journal, 2020)
Rattus norvegicus is one of the experimental animals that is widely used in research. Knowing the hematological status of R. norvegicus rats during reproduction is the aim of this study. In this study was used 12 female rats were sexually mature. Data were collected at the rats that were not yet pregnant (T0); 10 days pregnant mouse (T10); 20 days pregnant mouse (T20); 7-day lactated rat (L7); and 20-day lactating mice (L20). This study shows that during pregnancy and breastfeeding there is an increase in the level of erythrocytes in the blood. During pregnancy, there is a decrease in hemoglobin levels and higher during lactation. The hematocrit value during lactation shows a higher value than in the non-pregnant and pregnant states.